BODY MASS INDEX (BMI) DAN LAMA MENOPAUSE BERPENGARUH TERHADAP KUALITAS HIDUP MENOPAUSE (Studi di Desa Karang Jeruk Kecamatan Jatirejo Kabupaten Mojokerto) - DWI SYALFINA, AGUSTIN (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2017)
Menopause of woman life is natural process and must be experienced by every woman. Normally menopause in 40 until 60 years. Menopause has many symptoms that vasomotor symptoms, fisic symptoms, psicosocial symptoms and sexual symptoms. The symptoms of menopause influnced quality life of menopause. The objectives of this study is to analysis of factor quality life of menopause. This study designed by cross-sectional design. Samples taken by simple random sampling. Samples of this study as many as 105 respondents who menopause mother , can read, good communication and cooperative. Variables independent of this study are age, education, employment, body mass index, number of child, menopausal stage. Variabel dependent are quality life of menopause. Data collected with interview and MQOL (Menopause Spesific Quality Of Life ) instrument.The results showed the all of respondents has aged on normally menopause, and majority with lower education, unemployment and has 2 until 5 of child. Body mass index and menopausal stage has same proportion of each other categorical. Bivariat analysis showed that associated signifikan between education, employment, body mass index, menopausal stage with quality life of menopasuse. Using by the logistic regression, the results showed that Body mass index has effected with quality life of menopasuse .Health workers must do early detection or screening should be a continue assessment in quality life of menopause. That di decresase symptoms of menopause and increase quality life of menopause.Keyword : quality life, menopause, Body mass index, menopausal stage